IoT BASED SMART SOLID WASTE COLLECTION SYSTEM IN MIST CAMPUS - KAMRUZZAMAN, F. A. M; RIPON, MD. RIDWANUL ISLAM (My University, 2024)
Effective solid waste collection is crucial for upholding environmental sustainability and public health in educational institutions. This paper introduces an Internet of Things (IoT) solid waste management system created for the Military Institute of Science and Technology (MIST) campus. The system uses IoT sensors to monitor odor and garbage levels at specific waste disposal areas throughout the campus. IoT sensors are strategically positioned within the waste bins to constantly monitor factors like odor concentration and garbage fill levels. The sensors are linked to a central data processing unit via a wireless network, allowing for real-time data gathering and analysis. The technology utilizes data analytics and machine learning algorithms to forecast garbage accumulation tendencies and enhance waste pickup schedules. Campus authorities can use this technology to effectively oversee garbage disposal activities, ensuring prompt collection and avoiding overflow or unpleasant odors. This IoT-driven solid waste management system provides benefits such as increased efficiency, fewer labor expenses, and greater environmental monitoring capabilities compared to conventional manual approaches. It encourages sustainable practices through data-driven decision-making and appropriate waste management habits throughout the community. The system implemented at the MIST campus shows a viable approach to upgrading solid waste management methods by focusing on reducing odor problems and improving waste collection processes
IoT Based Smart Solid Waste Collection System in MIST Campus